Oncostatin M Maintains Naïve Pluripotency of mESCs by Tetraploid Embryo Complementation (TEC) Assay - Ye, Xiaoying; Tian, Chenglei; Liu, Linlin; Feng, Guofeng; Jin, Kairang; Wang, Haiying; Chen, Jiyu; Liu, Lin (Frontiers in Cell and Developmental Biology, 2021)
It has been well established that leukemia inhibitory factor (LIF) is essential for maintaining naïve pluripotency of embryonic stem cells (ESCs). Oncostatin M (OSM) is a member of the IL-6 family of cytokines which share gp130 as a receptor subunit, and the OSM-gp130 complex can recruit either LIF receptor β or OSM receptor β. Here we show that OSM can completely replace LIF to maintain naïve pluripotency of ESCs. Mouse ESCs (mESCs) cultured in the presence of LIF or OSM not only express pluripotency genes at similar levels but also exhibit the same developmental pluripotency as evidenced by the generation of germline competent chimeras, supporting previous findings. Moreover, we demonstrate by tetraploid embryo complementation assay, the most stringent functional test of authentic pluripotency that mESCs cultured in OSM produce viable all-ESC pups. Furthermore, telomere length and telomerase activity, which are also crucial for unlimited self-renewal and genomic stability of mESCs, do not differ in mESCs cultured under OSM or LIF. The transcriptome of mESCs cultured in OSM overall is very similar to that of LIF, and OSM activates Stat3 signaling pathway, like LIF. Additionally, OSM upregulates pentose and glucuronate interconversion, ascorbate and aldarate metabolism, and steroid and retinol metabolic pathways. Although the significance of these pathways remains to be determined, our data shows that OSM can maintain naïve pluripotent stem cells in the absence of LIF.